The Impact of High-Intensity Interval Training on Brain Derived Neurotrophic Factor in Brain: A Mini-Review - Jiménez-Maldonado, Alberto; Rentería, Iván; García-Suárez, Patricia C.; Moncada-Jiménez, José; Freire-Royes, Luiz Fernando (Frontiers in Neuroscience, 2018)
The brain-derived neurotrophic factor (BDNF) is a protein mainly synthetized in the neurons. Early evidence showed that BDNF participates in cognitive processes as measured at the hippocampus. This neurotrophin is as a reliable marker of brain function; moreover, recent studies have demonstrated that BDNF participates in physiological processes such as glucose homeostasis and lipid metabolism. The BDNF has been also studied using the exercise paradigm to determine its response to different exercise modalities; therefore, BDNF is considered a new member of the exercise-related molecules. The high-intensity interval training (HIIT) is an exercise protocol characterized by low work volume performed at a high intensity [i.e., ≥80% of maximal heart rate (HRmax)]. Recent evidence supports the contention that HIIT elicits higher fat oxidation in skeletal muscle than other forms of exercise. Similarly, HIIT is a good stimulus to increase maximal oxygen uptake (VO2max). Few studies have investigated the impact of HIIT on the BDNF response. The present work summarizes the effects of acute and long-term HIIT on BDNF.